2013
DOI: 10.1371/journal.pone.0055419
|View full text |Cite
|
Sign up to set email alerts
|

Reversed Dipper Blood-Pressure Pattern Is Closely Related to Severe Renal and Cardiovascular Damage in Patients with Chronic Kidney Disease

Abstract: BackgroundA non-dipper blood pressure (BP) pattern is very common in chronic kidney disease (CKD) patients and affects the progression and development of cardiovascular disease. However, data on the reversed dipper BP pattern on target-organ damage in Chinese CKD patients are lacking.MethodsA total of 540 CKD patients were enrolled. Ambulatory blood pressure monitoring (ABPM), clinical BP, ultrasonographic assessment and other clinical data were collected. Univariate and multivariate analyses were used to asce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
80
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 24 publications
6
80
0
2
Order By: Relevance
“…The presence or absence of antihypertensive treatment did not contribute to change the BP pattern described here. Consistent with our results, several previous studies described an association between albuminuria and circadian ambulatory BP in patients with diabetes or CKD (13)(14)(15)(16)(17). However, unlike our study, most of the previous studies had relatively small sample sizes (a few hundred patients), and, more importantly, they focused on nighttime nondipping or isolated nocturnal hypertension, whereas we used nighttime BP as a continuous variable, allowing for the quantification of nocturnal BP differences across albuminuria groups.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The presence or absence of antihypertensive treatment did not contribute to change the BP pattern described here. Consistent with our results, several previous studies described an association between albuminuria and circadian ambulatory BP in patients with diabetes or CKD (13)(14)(15)(16)(17). However, unlike our study, most of the previous studies had relatively small sample sizes (a few hundred patients), and, more importantly, they focused on nighttime nondipping or isolated nocturnal hypertension, whereas we used nighttime BP as a continuous variable, allowing for the quantification of nocturnal BP differences across albuminuria groups.…”
Section: Discussionsupporting
confidence: 82%
“…Several studies (13)(14)(15)(16)(17) have associated the circadian rhythm of BP to proteinuria/albuminuria in patients with diabetes and/or CKD. Additionally, previous data from our group showed that high albuminuria (30-300 mg/g creatinine) is associated with nighttime systolic BP (SBP) in treated and untreated patients with hypertension and in those with resistant hypertension (18,19).…”
mentioning
confidence: 99%
“…Our previous study suggested that age is independently correlated with the estimated glomerular filtration rate (eGFR), proteinuria and reverse dipper pattern of blood pressure in Chinese CKD patients [17]. We believe that age could play a key part in CKD and CVD based on previous data.…”
Section: Introductionmentioning
confidence: 89%
“…This is in contrast to an investigation that found a cross-sectional association of dipping an LV mass. 23 Which component of ambulatory BP should be used for the diagnosis of MUCH is a matter of debate. The conventional definition uses the awake ambulatory BP for making a diagnosis of MUCH.…”
Section: Discussionmentioning
confidence: 99%